Flipping houses for dummies - Roberts, Ralph R. 1958-; Kraynak, Joe (Tantor Audio, 2019)
Buy it, fix it, flip it! Are you a wanna-be flipper looking to get the property, get the job done, and get out-all while maximizing your profit? Not just another house-flipping book, this hands-on guide shows you how to roll up your sleeves and find the perfect property, secure a mortgage, negotiate with condo associations, increase curb appeal, and much more. Flipping a house is more than just buying, updating, and selling. To be successful, you have to be a bit fearless, highly organized, and, at times, creative. This new edition of Flipping Houses For Dummies gives you practical guidance on the risks and rewards of flipping properties; helps you determine whether you have the time, energy, cash, and other resources to be successful; and then conveys the expert knowledge you need to succeed in a very competitive market. &#9679 Find, fix, and sell houses for profit &#9679 Score bank-owned and foreclosed properties &#9679 Identify the best improvements for maximum ROI If you're ready for hard work and big profits, start flipping!
Online resource; title from title details screen (OverDrive, September 26, 2019)
Keywords: Flipping (Real estate investment) -- Handbooks, manuals, etc; Real estate investment -- Handbooks, manuals, etc -- United States; House buying -- Handbooks, manuals, etc -- United States; House selling -- Handbooks, manuals, etc -- United States; Dwellings -- Handbooks, manuals, etc -- Remodeling -- United States; Immeubles; Investissements; États-Unis; Guides, manuels, etc; Habitations; Achat; États-Unis; Guides, manuels, etc; Habitations; Vente; États-Unis; Guides, manuels, etc; Habitations; Réfection; États-Unis; Guides, manuels, etc; HOUSE & HOME; General; Dwellings; Remodeling; Flipping (Real estate investment); House buying; House selling; Real estate investment; United States; Downloadable audio books; Audiobooks; Handbooks and manuals; Livres audio